Answer:
we will have to multiply the second equation by 3 to eliminate the y variable by adding.
Step-by-step explanation:
Given the equations
4x – 3y = 6 → (1)
6x + 2y = 10 → (2)
As the first equation is multiplied by 2,
2(4x – 3y) = (2)6
8x - 6y = 12 → (3)
As we have to eliminate y,
so multiply the second equation by 3,
6x + 2y = 10
3(6x + 2y) = 3(10)
18x + 6y = 30 → (4)
So now adding the new equations (3) and (4) will eliminate the y variable by adding
8x - 6y = 12
18x + 6y = 30
--------------------
26x + 0y = 42
26x = 42
x = 42/26
x = 21/13
Therefore, we will have to multiply the second equation by 3 to eliminate the y variable by adding.